Optimizing Digital Promotional Graphic Design Strategies Using the AIDA Model - Rahardja, Untung; Aini, Qurotul; Supriati, Ruli; Al Hafiz, Mohammad Aditya (ADI Publisher, 2026)
The rapid growth of digital platforms has intensified competition in online marketing, requiring organizations to adopt more strategic, adaptive, and data-driven promotional approaches. Digital promotional graphic design plays a crucial role in capturing consumer attention and delivering persuasive messages across various platforms. However, differences in platform characteristics and user behavior may influence the effectiveness of these visual strategies, highlighting the need for a more structured design approach. This study aims to optimize digital promotional graphic design strategies by integrating the AIDA model (Attention, Interest, Desire, and Action) into visual communication practices to improve audience engagement and promotional effectiveness. This research employs a qualitative descriptive approach, combining literature review and visual content analysis. Digital promotional designs from various online platforms were systematically analyzed using AIDA indicators, supported by engagement metrics as secondary data to strengthen the evaluation of design effectiveness. The findings indicate that integrating data-driven analytics with the AIDA model significantly enhances the effectiveness of digital promotional graphic design. Visual optimization improves attention, structured and relevant content sustains interest, emotional and value-based messaging stimulates desire, and clear, strategically placed Call To Action (CTA) elements effectively encourage user action. This study concludes that the combination of the AIDA framework and data- driven decision-making provides a comprehensive and strategic foundation for optimizing digital promotional graphic design, ultimately improving communi- cation effectiveness and promotional performance in the digital era.